2019
DOI: 10.3389/fphar.2019.00229
|View full text |Cite
|
Sign up to set email alerts
|

[Ru(bpy)2(NO)SO3](PF6), a Nitric Oxide Donating Ruthenium Complex, Reduces Gout Arthritis in Mice

Abstract: Monosodium urate crystals (MSU) deposition induces articular inflammation known as gout. This disease is characterized by intense articular inflammation and pain by mechanisms involving the activation of the transcription factor NFκB and inflammasome resulting in the production of cytokines and oxidative stress. Despite evidence that MSU induces iNOS expression, there is no evidence on the effect of nitric oxide (NO) donors in gout. Thus, the present study evaluated the effect of the ruthenium complex donor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…Gout is characterized by severe articular inflammation and pain induced by MSU deposition precipitated by activation of transcription factors ( 19 , 20 ). Pre-experimentation and confirmation findings in our study demonstrated that transcription factor NFIL3 promoted the transcription of REDD1, induced a subsequent inhibition of mTOR pathway, and enhanced the neutrophil autophagy and NET formation, consequently preventing the inflammatory response of gout.…”
Section: Discussionmentioning
confidence: 99%
“…Gout is characterized by severe articular inflammation and pain induced by MSU deposition precipitated by activation of transcription factors ( 19 , 20 ). Pre-experimentation and confirmation findings in our study demonstrated that transcription factor NFIL3 promoted the transcription of REDD1, induced a subsequent inhibition of mTOR pathway, and enhanced the neutrophil autophagy and NET formation, consequently preventing the inflammatory response of gout.…”
Section: Discussionmentioning
confidence: 99%
“…MSU can trigger the release of some key pro‐inflammatory cytokines and chemokines, including IL‐6, TNF‐α, CXCL1, and CXCL2 (Rossaneis et al, ; Ryckman et al, ; Staurengo‐Ferrari et al, ). We proceeded to examine the effects of eucalyptol on expression of these cytokines and chemokines in ankle joint tissues, compared with theeffects of indomethacin.…”
Section: Resultsmentioning
confidence: 99%
“…Antileishmanial 213,214 and anti-inflammatory (as caused by gout arthritis) 215 activities of cis-[Ru(L) 2 (SO 3 )(NO)](PF 6 ), where L = bipyridine, were also reported recently. Anti-asthmatic complexes, cis-[Ru(L 1 ) 2 (L 2 )(NO)](PF 6 ) 3 , where L 1 = 2,2′-bipyridine, L 2 = 2-methyl-1Himidazole, 216 and [Ru(NO)(L 1 )(L 2 )] 3+ , where L 1 = terpyridine, L 2 = 1,2-benzoquinone-diimine, 217 were recently reported as well.…”
Section: Ruthenium Nitrosyl Complexes As Potential Anticancer Drugsmentioning
confidence: 73%